Fenologia do buriti (Mauritia flexuosa L.f.) no Norte de Minas Gerais - Karoline Paulino Costa (2017)
The Cerrado is currently one of the world's biodiversity hotspots, with veredas being one of its phytophysiognomies where occurs the buriti (Mauritia flexuosa L. f.). The buriti is a palm tree with a variety of uses, especially fruit with pulp with a high content of carotenoids, vitamin A and -tocopherol, which has aroused the interest of the food and cosmetic industries. The pulp (dehydrated pulp) is obtained by means of extractivism, but there is no management plan established for the north of Minas, which makes possible the production planning and the conservation of the species, and for this it is fundamental to know its phenological behavior. Thus, the objective was to characterize the phenological behavior of Mauritia flexuosa L. f. in the northern region of Minas Gerais, and to relate the influence of climate on these events. For this purpose, palms of Buriti were evaluated for two years in trails of the cities of Brasília de Minas, Lontra and Cônego Marinho, located in the north of Minas Gerais. Fifteen female and five male plants were sampled in each lane, with diameter at breast height (DBH) and height (H) determined at the first evaluation. The following phenotypes were recorded monthly: leaf emission, green and senescent leaves, spadix emission, floral bud, emitted flower, immature and mature fruits. The phenological events were quantified based on intensity and activity indexes, which were later correlated with meteorological data of the region (temperature and precipitation). The average value of DBH and H, were 0.4 m and 11 m, respectively. The three populations showed constant vegetative phenology during the two years of evaluation. Phenophases belonging to the reproductive cycle occurred predominantly in the second year of evaluation, with high synchrony between the individuals, according to the activity index. The presence of immature and mature fruits was observed during the two years of evaluation; however, all mature fruits were from flowering prior to the study period. The phenological events did not present a correlation pattern between activity and intensity indices and meteorological factors. Therefore, it is concluded that the buriti has a phenological pattern classified as supra-annual, and that there is no influence of the meteorological factors on the buriti phenology in the north of Minas Gerais.